2022
DOI: 10.1101/2022.02.16.22271050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnic inequities in multimorbidity among people with psychosis: A retrospective cohort study

Abstract: Background Research shows persistent ethnic inequities in mental health experiences and outcomes, with a higher incidence of illnesses among minoritised ethnic groups. People with psychosis have a higher risk of multiple long-term conditions (MLTC; multimorbidity). However, there is limited research regarding ethnic inequalities in multimorbidity in people with a schizophrenia spectrum disorder. This study investigates ethnic disparities in physical health multimorbidity in a cohort of people with psychosis. M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent analysis of ethnic inequalities in physical health MLTCs among people with psychosis living in the UK found that Black people were at higher risk of psychosis compared to white people 64 . The differences between our findings and those of de Freitas and colleagues could be attributed to the fact that the de Freitas study included people under 18 years (age range 13 to 65) and focused on people with a particular type of severe mental illness: psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of ethnic inequalities in physical health MLTCs among people with psychosis living in the UK found that Black people were at higher risk of psychosis compared to white people 64 . The differences between our findings and those of de Freitas and colleagues could be attributed to the fact that the de Freitas study included people under 18 years (age range 13 to 65) and focused on people with a particular type of severe mental illness: psychosis.…”
Section: Discussionmentioning
confidence: 99%